Ultrasonographic assessment of thyroid volume in oldest-old individuals - Duarte,Glaucia Cruzes (2017)
ABSTRACT Objective The aim of this study was to describe the relationship between thyroid volume and age, gender, anthropometric characteristics, and echogenicity in oldest-old subjects in an iodine-sufficient area. Subjects and methods The study included 81 independent elderly individuals aged ≥ 80 years (65 [80.2%] women). We determined these individuals’ anthropometric characteristics, body mass index (BMI), and lean body mass, as well as thyroid volume and echogenicity by ultrasonography. Results We observed that octogenarians and nonagenarians had different profiles of thyroid echogenicity. The volume of the thyroid was smaller in nonagenarians than octogenarians (p = 0.012, r = 0.176), and subjects aged 80–89 years had more often hypoechoic glands than those aged ≥ 90 years (p = 0.01 versus 0.602). Conclusion The identification of ultrasonographic differences in oldest-old individuals will contribute to establishing preclinical markers, such as echogenicity, to identify individuals at risk of developing autoimmune thyroid disease. Future prospective studies should identify if 80–89-year-old individuals with hypoechoic glands progress to hypothyroidism, and if the absence of changes in echogenicity (i.e. a normal thyroid parenchyma) would have a positive impact on longevity among nonagenarians.